Urban Runoff Control and Sponge City Construction - Jia, Haifeng; Hu, Jiangyong; Huang, Tianyin; Chen, Albert S.; Ma, Yukun (2022)
The rapid urbanization, sometimes lacking adequate planning and design, has led to worsening city syndrome situations, such as urban flooding, water pollution, heat island effects, and ecologic deterioration. Sponge city construction have become the new paradigm for a sustainable urban stormwater management strategy. Deviating from the traditional rapid draining approach, the new paradigm calls for the use of natural systems, such as soil and vegetation, as part of the urban runoff control strategy. It has become a widespread focus in urban water management research and practices globally. In this Special Issue reprint, there are 13 original scientific articles that address the different related urban runoff control issues. We are happy to see that all papers presented findings characterized as innovative and methodologically new. We hope that the readers can enjoy and learn deeply about urban runoff control and sponge city construction using the published material, and we hope that sharing of the researches results with the scientific community, policymakers and stakeholders can prompt the urban runoff control and sponge city construction globally.